Multicriteria evaluation of operational effectiveness of freight diesel locomotives on Lithuanian railways - Bureika, Gintautas (Transport, 2011)
The paper analyses and assesses the operating expenses of freight Diesel locomotives 2M62, 2M62K, 2M62M and ER20CF, suggesting the ways of their reduction. Given the damages of the old locomotive M62 and the structure of its operating expenses, some methods of Diesel locomotives’ upgrading are offered. Service life of new generation Diesel locomotives SIEMENS ER20CF and the locomotives 2M62K, 2M62M after the upgrade are determined. The taxes on air pollution by the exhaust gases of Diesel engines are calculated for the locomotives of each series. The effectiveness of operation of freight Diesel locomotives is calculated by three multicriteria evaluation methods and the most efficient freight Diesel locomotive for Lithuanian Railways is determined based on a set of criteria. Basic conclusions are also given. First Published Online: 12 Apr 2011